(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Context: The food security differs at different levels, global to regional and national to household and individual level because food security is deemed to be a multidimensional phenomenon encompassing climate change, civil conflicts, natural disasters, and social norms.